Teia Multicultural: a construção de um modelo inovador na escola brasileira - Correa, Georgia Carolina Piacentini (2018)
This research is about the significance of art, specially through theatre and self knowledge in the constitution of a school curriculum, as well with the Preschool, Pre-kindergarten, Elementary, Middle and High school teacher‟s formation process, allowing them to serve as research and development guides of all the contents that are relevant for these educational segments, demonstrating how these references can guide and provide all the contents proposed by the National Curriculum Base, specially when they are suggested from interdisciplinary projects, and yet extending the opportunity of new experiences for the students allowing them to unveil their gifts and skills. Art and self knowledge as tools in the educational process are presented based on the story of the author‟s life, and also, how they became efficient instruments on the pedagogic process that is developed in Teia Multicultural, and it is presented step by step from the school‟s Project construction, passing by the several stages of it‟s implementation, as well as all the chalenges that appeared during these 13 years since it‟s constitution, wich started only with Preschool, Pre-kindergarten, Elementary and Middle school until today, with your proposal beeing oriented by art and self knowledge from Preschool to High school. The pedagogic proposal of the school, oriented by art and self knowledge, has in it‟s construction the desire to allow the students, whatever their age, an effective, significant and pleasurable learning process, integrating cognitive, affective and motor skills aspects, resulting in a integral education. For this investigation we use as starting points some educational thinkers, recent researches wich point the “Learning based in projects” (ABP) as a possibility of a significant way of learning, and also the references from the interdsciplinary work specially under Dra. Ivanir Fazenda‟s perspective. Thus, we begin from the school learning, realized from interdisciplinary projects, that support all the pedagogic project wich, by the way, enable the school to be recognized as an innovating institution of integral learning by MEC (Ministry of Education) and also by The Edumission